Campanularia africana Stechow 1923 - Gil, Marta; Ramil, Fran (Zenodo, 2021)
Campanularia africana Stechow, 1923 Fig. 3G–H; Table 5 Campanularia africana Stechow, 1923: 104. Campanularia africana – Leloup 1938: 13–14, fig. 9. — Millard 1975: 204, fig. 67a. Material examined SOUTH ATLANTIC OCEAN • 2 colonies, growing on algae, without gonothecae; Vema Seamount, stn BT5; 31°37′16″–31°36′58″ S, 8°22′37″–8°23′06″ E; 71–94 m depth; 31 Jan. 2015; SEAFO-2015 leg.; SEAFO-2015-40437, SEAFO-2015-40768, LZM-UV slide R. 577. Distribution Campanularia africana has previously been reported from Australia (Watson 1990), Japan (Stechow 1923; Leloup 1938; Hirohito 1995) and Natal, South Africa (Millard 1975). Its bathymetric distribution extends from the littoral area to a depth of 102 m (Millard 1975; Stechow 1925). Our finding of C. africana at Vema Seamount represents the first record of this species for the Atlantic Ocean. : Published as part of Gil, Marta & Ramil, Fran, 2021, Hydroids (Cnidaria, Hydrozoa) from the Vema and Valdivia seamounts (SE Atlantic), pp. 49-96 in European Journal of Taxonomy 758 on page 62, DOI: 10.5852/ejt.2021.758.1425, http://zenodo.org/record/5088125 : {"references": ["Stechow E. 1923. Uber Hydroiden der Deutschen Tiefsee-Expedition, nebst Bemerkungen uber einige andre Formen. Zoologischer Anzeiger 53 (9 - 10): 223 - 236.", "Leloup E. 1938. Quelques hydropolypes de la baie de Sagami, Japon. Bulletin du Musee royal d'Histoire naturelle de Belgique 14 (28): 1 - 22.", "Watson J. E. 1990. Studies on Australian Hydroids. The genus Eudendrium and the fauna of the seagrass Amphibolis. Unpublished D. Phil. Thesis, University of Deaking.", "Hirohito Emperor of Japan. 1995. Hydroids of Sagami Bay II. Thecata. Publications of the Biological Laboratory, Imperial Household, Tokyo.", "Stechow E. 1925. Hydroiden der Deutschen Tiefsee-Expedition. Wissenschaftliche Ergebnisse der Deutschen Tiefsee-Expedition auf dem Dampfer \" Valdivia \" 1898 - 1899 27: 383 - 546."]}